Realistic simulation training in wound and dressing care: an experience report (Research, Society and Development, 2022)
Objective: to report the experience lived in the process of continuing education to nursing professionals from the realistic simulation for the treatment of wounds. Methods: This is a descriptive, participatory, convergent care study with a qualitative approach. The descriptive study is common in the field of education, in which the focus is to describe in more depth the behavior of the phenomena/people inserted in a reality Results and discussion: As a result, three contributions were listed: adequacy of the sterile dressing technique; adequate choice of dressing, prescription and management of dressings based on the assessment of the lesion; importance of carrying out permanent education considering learning methods that favor the improvement of wound care. Conclusion: Continuing education is a fundamental tool for improving care for complex wounds, being facilitated by the realistic simulation method, there is a greater assimilation of content and practical skills through this methodology, there is a lack in the process of knowledge about of dressings by nurses, being essential to educate them on the subject.